Separação da enzima frutosiltransferase produzida por Aspergillus oryzae IPT-301 em uma coluna de bolhas e espuma - Oliveira, Marcela Fernandes De (2018)
Fructooligosaccharides (FOS) are sugars with important functional properties. They are catalyzed by inulin hydrolis reactions or by the transfructosylation reaction from sucrose. The enzyme responsible for the formation of FOS from sucrose is the fructosyltransferase. Industrially this enzyme is obtained from microorganisms, among them there are some types of fungi like genus Aureobasidium, Penicillium and Aspergillus. The production of FOS directly from the enzyme, instead of the fermentation process carried out by the microorganism, allows the use of optimum conditions of catalysis for this biocatalyst. Due to the growing national demand for FOS, the development of national technology aimed at the separation and recovery of fructosyltransferase enzyme is of a great importance. Thus, this work aims to recover the enzyme fructosyltransferase produced from the fungus Aspergillus oryzae IPT-301. In order to perform this study, the process was carried out in a column of bubble and foam, where the pH, dilution of medium and concentration of the surfactant Tween 80 ® added was carefully studied. Foaming capacity for the process was obtained by addition of concentrations between 0.5 and 2% (w/v) Tween 80®. The results of enzymatic activity indicated that the concentration of 1% (w/v) of Tween 80 added to the medium after fermentation caused an increase in the transfructosylation activity (At) and reduction of the hydrolytic activity (Ah), reaching values ​​of 22.47 and 1.60 U.mL-1, respectively. The bubble and foam column tests indicated that use of 0.5% and 1.5% (w/v) surfactant to fermented broth with 1:2 (v/v) dilution and without dilution, respectively, at pH 5.5 achieved better results. The Dumas method, used to determine proteins, proved to be inadequate for the determination of enzyme concentration in the studied systems, most probably due to their concentration being below the limit of quantification of the equipment.